Leucismo en el Cucarachero Chupahuevos (Campylorhynchus griseus) en Colombia - Chica de Aguas, Eliana; Chacón Pacheco, Julio; Ballesteros Correa, Jesús (Nuestras Aves, 2015)
Este artículo no cuenta con un resumen.